Facebook and its Impact on Students' Learning Achievement at State Islamic High School of Palopo - Nurdin Kaso; Andi Nurjihad; Dodi Ilham; Nurul Aswar (Universitas Cokroaminoto Palopo, 2021)
This study aims to determine the impact of Facebook on student's achievement at the State Islamic High School of Palopo. This quantitative descriptive research conducted at State Islamic High School of Palopo, especially class XI IPA. The population consisted of 65 students, and the instruments used were questionnaires and interviews. The study results found no impact between accessing Facebook on the learning achievement of class XI State Islamic High School of Palopo students, evidenced by the calculated r-value of the variable accessing Facebook of 0.191 with a significance value of 0.280. Therefore, the calculated r-value is smaller than the r table (0.191 < 0.339) and the significance value (p) is greater than the 5% significance level (0.280 > 0.05). The existence of activities to access Facebook for students of State Islamic High School of Palopo with internet social media can also maintain student learning achievement.